Analysis and Validation of Dipole Moment Calculations in Chemistry Teaching - Bastos, Cristiano Costa; Leite, Bruno Silva (Orbital: The Electronic Journal of Chemistry, 2017)
In this paper, we analyze and validate of an alternative proposal for the understanding and interpretation of the dipole moment of diatomic molecules, content present in the curriculum of disciplines physical chemistry and quantum chemistry in undergraduate chemistry courses. For this, 87 students participating the degree course in chemistry at a university in Brazil, they used computational chemistry calculations and analytical calculations for the dipole moment of the considered molecules. Results show the proposed method can be an alternative for calculations involving dipole moment of diatomic molecules. DOI: http://dx.doi.org/10.17807/orbital.v9i5.1020